Effectiveness of Trigona laeviceps Propolis Extract Against Colletotrichum acutatum and Chili Damping-Off Disease - Hersanti; Andika Alif Suangga; Ichsan Nurul Bari (Jurnal Biodjati, 2026)
Indonesia’s biodiversity provides natural resources with potential for pest and plant disease control. Propolis from Trigona laeviceps has antimicrobial properties and can serve as an environmentally friendly alternative. The fungus Colletotrichum acutatum causes anthracnose disease in chilies, reducing plant production. This study aims to test the effectiveness of ethanol extract of T. laeviceps bee propolis in inhibiting the growth of C. acutatum in vitro and suppressing red chili damping-off. The experiment was carried out at the Phytopathology Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Padjadjaran. The research was conducted using a Completely Randomized Design (CRD) with two stages, and the data were analyzed using ANOVA followed by Duncan’s multiple range test (DMRT). The first stage is a test to determine the Lethal Concentration 50% (LC50) of propolis ethanol extract, yielding an LC50 of 12.8%. The second stage involved evaluating the ethanol extract of propolis using the poisoned food technique to assess its effects on colony growth and conidia germination of Colletotrichum acutatum, as well as its ability to suppress red chili damping-off.  The experiment consisted of four treatments of propolis ethanol extract with concentrations of 12.8%, 19.2%, 25.6%, and 32%, a mancozeb fungicide treatment, and a control treatment. Repetition was carried out four times. T. laeviceps propolis ethanol extract concentrations of 12.8%, 19.2%, 25.6%, and 32% were effective in inhibiting the growth of C. acutatum fungal colonies with an inhibition range of 56.94%, 60.28%, 65.28%, and 81.39%, respectively. The ethanol extract of T. laeviceps propolis at concentrations of 25.6% and 32% reduced the incidence of red chili sprout blight by 37.5% and 35%, respectively.